Additive manufacturing enabled drug delivery features for titanium-based total hip replacement cementless femoral stems - Bezuidenhout, Martin Botha (Stellenbosch : Stellenbosch University, 2015)
Thesis (MEng)--Stellenbosch University, 2015.